High flow nasal oxygen therapy in preventing post Extubation Hy-Poxaemia and postoperative pulmonary complications: a systematic review and meta-analysis - Tan, Jamie; Izaham, Azarinah; Abd Rahman, Raha; Md Ralib, Azrina; Chin, Kok Yong; Teo, Rufinah; Maaya, Muhammad; Muhammad Yusof, Aliza (Malaysian Society of Anaesthesiologists and College of Anaesthesiologists, Academy of Medicine Malaysia, 2023)
BackgroundHigh flow nasal oxygen therapy (HFNOT) has gained popularity in recent years in the treatment of respiratory failure in post-extubation of non-surgical and surgical patients. This systematic review and meta-analysis investigated the role of HFNOT in reducing the incidence of postoperative pulmonary complications (PPC) and post-extubation hypoxaemia.MethodsA comprehensive search of PubMed, Scopus, EBSCOHost, ProQuest, Ovid MEDLINE and Web of Science was performed. Randomised controlled trials (RCTs) that com-pared HFNOT to conventional oxygen therapy (COT) during the postoperative period were identified. Data were pooled and estimates of effect were reported using odds ratio for dichotomous outcomes and mean difference for continuous outcomes, with 95% confidence intervals.ResultsSeventeen RCTs (n = 1761 patients) were included. Compared to COT, HFNOT re-duced the incidence of PPC (OR 0.66, 95% CI 0.47 – 0.91, p = 0.01), hospital length of stay (MD = -0.31, 95% CI -0.53 – -0.1, p = 0.004) and mortality rates (OR 0.3, 95% CI 0.11 – 0.82, p = 0.02). HFNOT also resulted in significantly higher PF ratio (MD 18.17, 95% CI 9.76 – 26.57, p < 0.0001). In the subgroup analysis, the incidence of PPC was significantly lower in patients who had HFNOT applied for more than 24 hours (OR 0.5, 0.28 – 0.88 95% CI) and in non-cardiothoracic surgeries (OR 0.57, 0.38 – 0.85 95% CI). PF ratio was also significantly higher in non-cardiothoracic surgeries (MD 32.36,19.88 – 44.84 95% CI). However, PF ratio was found to be better in the HFNOT group when applied for 24 hours or less (MD 33.96, 19.25 – 48.67 95% CI).ConclusionThis meta-analysis suggests that HFNOT reduces the incidence of PPC and improves PF ratio, resulting in less post-extubation hypoxaemia. It was associated with lower mortality rates and shorter length of stay in the hospital. Larger trials should be con-ducted to validate these findings.